PEMIDANAAN TERHADAP PERBUATAN MENGHILANGKAN MAYAT YANG DILAKUKAN ANAK (STUDI TERHADAP PUTUSAN MAHKAMAH AGUNG NO. 774K / PID.SUS / 2015) - Heppi Florensia; Mety Rahmawati (Jurnal Hukum Adigama, 2018)
Criminalization of the offender especially in the perpetrators of children under age is as a sanction that tells implied to someone who performs acts meet certain conditions. Often in prosecuting a criminal case the Public Prosecutor is wrong in deciding what articles should be imposed on the perpetrator. As one case of Supreme Court verdict No.774K/PID.SUS/2015 with 16-year-old defendant Dicky Pranata prosecuted by the Prosecutor with Article 340 of the Penal Code juncto Article 56 of the Criminal Code is a criminal act of premeditated murder, in which the elements of Article 340 of the Criminal Code are not fulfilled the defendant's self but the existence of other crimes Article 181 of the Criminal Code of disappearance committed by the defendant. The defendant was sentenced to 10 years in prison at the District Court, while the defendant was released from the sentence of the Court of Appeal and Cassation. The problem in this research is whether the act of the perpetrator fulfills the elements in Article 340 juncto Article 56 paragraph (1) of the Criminal Code juncto Article 1 paragraph (3) SPPA Act and Article 181 of the Criminal Code? How to base criminal offenses in the Supreme Court ruling case No.774K/PID.SUS/2015? The researcher examines the problem with normative juridical method. Based on the analysis result that the defendant is not proven to commit element of crime Article 340 KUHP, but the existence of criminal act Article 181 of Criminal Code which has been done by defendant.